Financial services and development in the Caribbean - Gonzales, Anthony P. (United Nations New YorkUS, 1993)
Attempts to provide a global and integrated picture of the state of the industry and the remedies that are needed. Looks at aspects such as foreign direct investment, transnational banks and financial development; trends and problems in the industry; possibilities for exporting; and regional co-operation and integration. Makes policy conclusions and suggestions.